Laparoscopic para‐aortic lymphadenectomy for colorectal cancer with clinically suspected lymph node metastasis. Issue 4 (8th November 2018) - Yamamoto, Seiichiro; Kanai, Toshio; Yo, Kikuo; Hongo, Kumiko; Takano, Kiminori; Tsutsui, Mai; Nakanishi, Ryo; Yoshikawa, Yusuke; Nakagawa, Motohito
Abstract: Introduction: The optimal surgical management strategy for isolated para‐aortic lymph node (PALN) metastases from colorectal cancer (CRC) remains unclear. However, the complication rates for open approaches remain high. In this study, the outcomes of laparoscopic para‐aortic lymphadenectomy in patients with clinically suspected PALN metastasis were evaluated. Methods: Between April 2013 and April 2018, we performed laparoscopic primary resection and para‐aortic lymphadenectomy in 11 patients with advanced colorectal cancer and clinically suspected PALN metastasis. This study was a single‐center, retrospective, case series analysis, and the surgical outcomes were reviewed. Results: There were no cases of perioperative mortality, and conversion to open surgery was necessary in only one patient (9%) because of invasion into a rib. One patient (9%) required a blood transfusion. Postoperative complications occurred in three patients, and the morbidity rate was 27% (3/11). Pathologically, PALN metastasis was confirmed in five patients (45%), all of whom received postoperative chemotherapy. The median survival time for all patients was 25 months, and one patient died of recurrence at 25 months after the initial surgery. Two other patients were alive with recurrence after 47 and 36 months, and two patients were alive without recurrence after 17 and 2 months. Conclusion: Laparoscopic para‐aortic lymphadenectomy for advanced colorectal cancer with clinically suspected PALN is technically feasible and may be beneficial in selected patients. It is necessary to investigate the feasibility of this procedure in a future case series, and information regarding true oncologic outcome will require long‐term follow‐up.